pH-dependent antibacterial activity of glycolic acid : implications for anti-acne formulations - Valle-González, Elba R. (2021)
Glycolic acid is the smallest alpha hydroxy acid and widely used for skincare applications, including to treat acne vulgaris. Oftentimes, high concentrations of glycolic acid (~20–50 vol%) are incorporated into chemical peels to reduce acne-related inflammation while there is an outstanding need to determine to what extent glycolic acid can potently inhibit Cutibacterium acnes (formerly known as Propionibacterium acnes), which is a Gram-positive bacterium implicated in acne pathogenesis. Herein, we report that glycolic acid exhibits pH-dependent antibacterial activity against C. acnes and mechanistic studies identified that the nonionic form of glycolic acid is more active than the anionic form. The degree of antibacterial activity, including minimum bactericidal concentration (MBC), of glycolic acid was evaluated in the pH range of 3 to 4.5, and the greatest potency was observed at pH 3. In light of skincare formulation needs, we selected the pH 3.5 condition for further testing and determined that glycolic acid kills C. acnes cells by disrupting bacterial cell membranes. While most conventional treatments involve high concentrations of glycolic acid (>20%), our findings support the potential of developing anti-acne formulations with glycolic acid concentrations as low as 0.2% and with pH conditions that are suitable for over-the-counter applications.